2010
DOI: 10.1002/sia.3224
|View full text |Cite
|
Sign up to set email alerts
|

Amine species on self‐assembled monolayers of ω‐aminothiolates on gold as identified by XPS and NEXAFS spectroscopy

Abstract: Functionalised surfaces are of interest in many fields, e.g. in biomedicine, materials science and molecular electronics. In this study a series of self-assembled aliphatic and aromatic monolayers on gold substrates with terminal amino groups was investigated. Four different thiol molecules were used: aliphatic 11-aminoundecane-1-thiol (AUDT), aromatic 4-aminobenzenethiol (ABT) and aromatic ω-amino thiols with an alkyl spacer as 4-aminophenylbutane-1-thiol (APBT) and 3-(4 -amino-1,1 : 4 ,1 -terphenyl-4-yl)prop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
45
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 46 publications
(48 citation statements)
references
References 19 publications
(30 reference statements)
3
45
0
Order By: Relevance
“…The spectrum from the PATP reference presents only two contributions at 399.0 eV (~90% of the total nitrogen contribution) corresponding to primary amino groups (− NH2 ) and at 401.4 eV belonging to protonated or hydrogen-bonded amino groups ( NH3  + , H … NH2 ) 23–25 . It was already shown that amino groups are the dominating species for aromatic molecules whereas it can be the opposite for aliphatic amines 23,24 . Instead, polymerised samples presented four contributions, previously observed on polyaniline films 26–29 .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The spectrum from the PATP reference presents only two contributions at 399.0 eV (~90% of the total nitrogen contribution) corresponding to primary amino groups (− NH2 ) and at 401.4 eV belonging to protonated or hydrogen-bonded amino groups ( NH3  + , H … NH2 ) 23–25 . It was already shown that amino groups are the dominating species for aromatic molecules whereas it can be the opposite for aliphatic amines 23,24 . Instead, polymerised samples presented four contributions, previously observed on polyaniline films 26–29 .…”
Section: Resultsmentioning
confidence: 99%
“…The line at 161.9 eV is attributed to thiol or thiolate strongly bonded to the gold surface 23,30–33 . The second doublet centred at 163.1 eV was previously ascribed to unbounded or non-chemisorbed thiol, thiolate or disulphide for high coverage 30,32,33 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The chemical state of the nitrogen in the AUT‐SAM was revealed by high‐resolution N‐1 s spectra (Figure ). Two species were observed: one was attributed to amine (―NH 2 ) groups (399.9 eV), and the other was attributed to protonated (or hydrogen‐bonded) amino groups (401.7 eV) . The relative proportion of the protonated amines (77%) is relatively greater than that of the ―NH 2 amines (23%).…”
Section: Resultsmentioning
confidence: 99%
“…Prior to treatment no significant nitrogen peak was observed, while after treatment with the block copolymer solution, peaks at 399 and 402 eV are clearly evident, which arise from the nitrogen‐containing PDMAEMA block and confirm the adherence of the block copolymer to the model surface. The peak at 399 eV is assigned to uncharged nitrogen atoms, while the peak at 402 eV is assigned to charged nitrogen atoms 70. Curve fitting of this region revealed that there was 79% uncharged and 21% charged nitrogen atoms.…”
Section: Resultsmentioning
confidence: 99%